Madurese Soap Opera: An Industry and Madurese Culture Migration of Situbondo People (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
The purpose of this study is to describe a variety of research problems, including the industrialization of Madurese soap opera and the Madurese cultural migration of the Situbondo community. The results showed that Madurese soap opera is a product of cultural industrialization that is produced based on the logic of mass cultures. Such as standardization, commodification, and massification. Standardization is seen from the use of local artists, Madurese dangdut music, as well as local narratives built through local phenomena in Situbondo. Cultural commodification can be seen from the changing motive of drama arts (Al Badar) to VCD films (Madurese soap opera). As a commodity, Madurese soap opera has an economic motivation that is demonstrated in terms of massification; it is produced in 10,000 pieces and distributed to the local market within East Java. Madurese soap opera is a phenomenon of the disruption of global industrial technology captured by local communities, acting as a comparison to the national soap opera industry. The contestation can be seen through both abilities in using global technology, namely television. Local television has a big role in promoting local content such as Madurese soap opera. Madurese soap opera on local television eventually became a medium that could bring people closer to their Madurese cultural identity.